Environmental sustainability practices in portuguese dental clinics - Cristina Bettencourt Neves; Nuno Santos; Sónia Mendes (Sociedade Portuguesa de Estomatologia e Medicina Dentária, 2022)
Objectives: To study the implementation of environmental sustainability practices at Portuguese dental clinics, the importance given by clinical directors to these practices, and the barriers felt in their applicability. Methods: This cross-sectional study's target population was clinical directors (Dentists or Stomatologists) working in Portugal. Data was collected through an online questionnaire shared in several groups of clinicians on social networks, published in digital journals, and sent by email through medical associations. It was available between February and April 2021. The questionnaire collected information about the implementation of environmental sustainability practices in dental clinics within six categories of management: devices and equipment, dental amalgam, imaging, paper, energy, and water. There were also questions about the importance of these practices and the barriers felt. Descriptive statistics of all variables were performed. Results: The sample included 245 clinical directors, of which 65.5% were female and 43.7% were between 40 and 49 years old. There was a high degree of implementation of environmental sustainability practices related to imaging (82.6%), dental amalgam (80.7%), water (67.5%), energy (67.4%), paper (63.4%), and devices and equipment (62.9%). Almost all respondents (96%) considered that environmental sustainability practices are important or very important, and the more frequently referred barriers to implementation were costs (44.6%) and lack of training/information (16.3%). Conclusions: Clinical directors showed good environmental awareness and satisfactory implementation of environmental sustainability practices in dental clinics. Costs were the most reported barrier to the implementation of further practices.